Philosophy and public affairs (Cambridge Cambridge University Press, 2000)
This collection of new essays derives from a conference sponsored by the Royal Institute of Philosophy and the Centre of Philosophy and Public Affairs at the University of St Andrews. It brings together a number of prominent academics from the fields of philosophy and political theory along with politicians and social commentators. The subjects covered include liberalism, education, welfare policy, religion, art and culture, and cloning. The mix of contributors and the topicality of the subject matter should further promote a serious engagement between philosophy and public life.
Includes bibliographical references and index.
Keywords: Public administration -Philosophy -Congresses